HUBUNGAN KECEMASAN ORANG TUA DENGAN INTERAKSI SOSIAL ANAK PADA MASA PANDEMI COVID-19 DI SDN CLAKET - MOJOKERTO - Devita Anggraini; Eka Diah Kartiningrum; Ika Suhartanti (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
This study aimed to know the correlation of parents’ anxiety with their children’s social interactions rate during the pandemic at SDN Claket, Mojokerto. Upon analyzing the data, it showed that 30 parents (52.6%) of them have moderate anxiety, and 38 students (66.7%) of them have high social interaction. It shows that there is correlation between parent’s worries and children’s social interaction during Covid-19 at SDN Claket, Mojokerto with the value of r count = 0.352 and p value = 0.007. Parent’s anxiety levels affected their children’s social interactions. More worries that parents have, resulted in less social interaction that the children get. The opposite also applies where less worries that the parents’ have, more social interaction that the children will get. Therefore, schools are suggested to hold counseling section to educate parents who have too high anxiety of their children’s social interaction to prevent them to receive psychological trauma.